Proceedings. 12th International Conference on Computer Communications and Networks (IEEE Cat. No.03EX712)
DOI: 10.1109/icccn.2003.1284149
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid optical network architecture consisting of optical cross connects and optical burst switches

Abstract: Optical burst switches (OBSes) have been proposed to improve the utilization of a network of optical cross connect (OXCs). Current studies on OBS assume a network consisting of OBSes alone. While this is a reasonable assumption for evaluating a new technology, the question of how a network of OXCs can be evolved to a network of OBSes has not been studied. In this paper, we propose a hybrid architecture consisting of OBSes at the network edge and OXCs in the network core. This architecture allows carriers to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Test-beds have been set up to demonstrate the feasibility of Optical Burst Switching (OBS) paradigm with a variety of switching devices [5, 6, 7 , 8, 9]. Performance evaluation of hybrid optical switches has been carried out [10,11,12,1] and the hybrid approach has been compared with the use of a single technology [13,14]. Furthermore, an initial design analysis of architectures for MG-OXe has been undertaken [15], and it has been shown that the performance of hybrid architectures is little different from that of switches equipped with fast technology only, while the cost and scalability of the hybrid approach are superior.…”
Section: A Multi-granular Optical Nodes and Networkmentioning
confidence: 99%
“…Test-beds have been set up to demonstrate the feasibility of Optical Burst Switching (OBS) paradigm with a variety of switching devices [5, 6, 7 , 8, 9]. Performance evaluation of hybrid optical switches has been carried out [10,11,12,1] and the hybrid approach has been compared with the use of a single technology [13,14]. Furthermore, an initial design analysis of architectures for MG-OXe has been undertaken [15], and it has been shown that the performance of hybrid architectures is little different from that of switches equipped with fast technology only, while the cost and scalability of the hybrid approach are superior.…”
Section: A Multi-granular Optical Nodes and Networkmentioning
confidence: 99%
“…Chou et al [11] presented a hybrid optical network architecture consisting of optical cross connects and optical burst switches. The architecture allows carriers to gradually migrate from an OXCbased network to an OBS-based network with improved network utilization.…”
Section: Introductionmentioning
confidence: 99%
“…1 Optical bursts with the same multiplexing/demultiplexing core node would not have to be switched in intermediate core nodes but could be transported together through the WSN in a direct lightpath instead as also illustrated in Figure 4.2. Such an interconnection of burst-switched nodes with direct lightpaths is also proposed in [OSHT01,CSBO03] as an OBS/OPS introduction scenario (cf. Section 2.3.4) and referred to as burst-over-circuit-switching (BoCS) here.…”
Section: Network Scenario For Burst Transportmentioning
confidence: 99%
“…The migration scenarios outlined in [OSHT01] and [CSBO03] define an extreme type of a client-server hybrid optical network. The client layer OBS nodes basically act as traffic aggregation nodes at the edge of the core network.…”
Section: Client-server Hybrid Optical Networkmentioning
confidence: 99%